Implementation of the Use of E-Tax Cards for the Collection of Non-Metallic Minerals and Rocks Tax in Lumajang Regency - Samadikun; Hara, Abubakar Eby; Poernomo, Djoko (GoAcademica Research & Publishing, 2024)
The transformation of e-government implementation allows local governments to innovate using information technology to improve their performance. One of the e-government innovations in the taxation sector that supports the increase in Local Own-Source Revenue (Pendapatan Asli Daerah) is the electronic collection of Non-Metallic Minerals and Rocks Tax (Pajak MBLB) implemented by the Lumajang Regency Government. The use of the E-Tax Card for MBLB has proven to increase tax revenue by 46% compared to the previous year's receipts and minimize the negative impacts of mining. This study aims to explain the factors influencing the implementation of the E-Tax Card for MBLB in collecting the Non-Metallic Minerals and Rocks Tax in Lumajang Regency. The theory used is a combination of Syahruddin's and George C. Edward III's theories, which include aspects of Policy Makers/Initiators, Field Officers, and Target Groups. This study employs a qualitative descriptive method with data collection techniques through interviews, documentation, and observations at portal units and mining sites. The research results indicate that the implementation of the E-Tax Card for MBLB in collecting the MBLB Tax in Lumajang Regency is less than optimal in the factors of bureaucratic structure, resources, and disposition.